Management of Penetrating Chest Injuries - Muhammad Ateeq , Shazia Jahan . Azhar Sajjad , Faisal .G. Bhopal (Journal of Rawalpindi Medical College, 2011)
Background: To determine the pattern of penetrating thoracic injury, including the causes, the role of surgery and intervention outcomes in general surgical unit. Methods: In this descriptive study patients of all age groups and either sex with isolated penetrating chest trauma or poly trauma were included. Results: Out of total 926 patients, studied during ten years period, 694 cases (74.94%) were medico legal. Haemopneumothorax was the most commonly observed consequence of penetrating chest injury. (n=539). Tube thoracostomy was performed in 855 (92.33%) cases.Acute Respiratory Distress Syndrome(ARDS) was the commonest complication(5.07%). Overall mortality rate was 08.96%. Conclusion: Timely rescue of patients, from site of accident, to the adequate health facility ensures better outcome